Petrogenesis and tectonic implications from the Ayishan Group in the South Qilian Belt, NW China. (23rd April 2020) - Sun, Yi; Niu, Manlan; Li, Xiucai; Wu, Qi; Cai, Qianru; Yuan, Xiaoyu; Li, Chen
Abstract : The Ayishan Group in the Lajishan area is sandwiched between the South Qilian Belt and the Qilian Block, which is transitionally interpreted to represent the products of the post‐collision setting or the continental marginal arc during the Early Ordovician or Silurian and is associated with the evolution of the Proto‐Tethyan Ocean. While the detailed information about the age, geochemistry, and tectonic setting of the Ayishan Group is lacking, our geological mapping and analyses demonstrates that the Ayishan Group consists of andesites, rhyolites, ignimbrites, sandstones, and conglomerates, which unconformably overlies the Cambrian–Ordovician arc‐ophiolite complex. Zircon U–Pb dating of the rhyolites demonstrated that the Ayishan Group formed between 447 and 442 Ma and is Late Ordovician. Geochemical analyses demonstrated that rhyolites have high and variable SiO2 contents of 69.6–76.5 wt% and an aluminium saturation index (A/CNK) of 0.85–1.45, belonging to calc‐alkaline to high K calc‐alkaline series. They are subdivided into two subtypes of high‐Sr/Y rhyolites (HSRs) and normal rhyolites (NRs) based on the geochemical characteristics. The HSRs show lower total rare earth elements (34.77–62.78 ppm), lower Yb (0.19–0.21 ppm) and Y (1.77–1.99 ppm) contents, and relatively higher Sr contents (159–193 ppm), compared with NRs, and with positive Eu anomalies. Both subtypes exhibit extremely high whole‐rock δ 18 O values of 12.63–13.21‰, but various initial 87 Sr/ 86 Sr ratios and ε Nd ( t ) values, indicating a dominant origin of terrigenous sediments and the HSRs exhibit a more terrestrial composition than the NRs. Various magma sources further caused the assorted residual phase leading to the different geochemistry between the HSRs and the NRs. Combined with the previous data, these results imply that the rhyolites of the Ayishan Group were produced in the process of the amalgamation of the Qilian Block with the Qaidam Block during the Late Ordovician, which further indicated that the Proto‐Tethyan Ocean closed 450 Ma ago.